2010
DOI: 10.1890/090037
|View full text |Cite
|
Sign up to set email alerts
|

Rising stream and river temperatures in the United States

Abstract: Water temperatures are increasing in many streams and rivers throughout the US. We analyzed historical records from 40 sites and found that 20 major streams and rivers have shown statistically significant, long‐term warming. Annual mean water temperatures increased by 0.009–0.077°C yr−1, and rates of warming were most rapid in, but not confined to, urbanizing areas. Long‐term increases in stream water temperatures were typically correlated with increases in air temperatures. If stream temperatures were to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
375
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 530 publications
(403 citation statements)
references
References 21 publications
(58 reference statements)
16
375
0
1
Order By: Relevance
“…Like numerous previous studies [Brown, 1969;Kaushal et al, 2010;Mohseni and Stefan, 1999], we found that air temperature is correlated with water temperature. However, air temperature has low variability in this (Table S3).…”
Section: Influences On Stream Temperaturesupporting
confidence: 89%
“…Like numerous previous studies [Brown, 1969;Kaushal et al, 2010;Mohseni and Stefan, 1999], we found that air temperature is correlated with water temperature. However, air temperature has low variability in this (Table S3).…”
Section: Influences On Stream Temperaturesupporting
confidence: 89%
“…The irregular-interval WT data are not ideal but also are not unique to our study (see Kaushal et al 2010 on-line materials). We analyzed the limitations of such data by two methods and the results were consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on WT trends in the mid-Atlantic region of the eastern USA indicates warming streams. Kaushal et al (2010) report that most streams examined in the midAtlantic region have statistically significant increasing WT trends. Seekell and Pace (2011) analyzed 100-year AT and WT records for the Hudson River Estuary, New York, and found statistically significant increasing trends in both.…”
mentioning
confidence: 99%
See 2 more Smart Citations